Comparing the effectiveness of virtual and semi-attendance Stress Inoculation Training [SIT] techniques in improving the symptoms of anxiety, depression, and stress of pregnant women with psychological distress: a multicenter randomized controlled trial - Atefeh Fatemi; Fatemeh Nasiri-Amiri; Mahbobeh Faramarzi; Mohammad Chehrazi; Hajar Adib Rad; Zeinab Pahlavan (BMC, 2023)
Abstract Background Some studies indicate that more than 10% of pregnant women are affected by psychological problems. The current COVID‐19 pandemic has increased mental health problems in more than half of pregnant women. The present study compared the effectiveness of virtual (VSIT) and semi-attendance Stress Inoculation Training (SIT) techniques on the improvement of the symptoms of anxiety, depression, and stress of pregnant women with psychological distress. Methods This study was conducted on 96 pregnant women with psychological distress in a 2-arm parallel-group, randomized control trial between November 2020 and January 2022. The semi-attendance SIT received treatment for six sessions, sessions 1, 3 and 5 as individual face-to-face and sessions 2, 4 and 6 as virtual once a week for 60 min continuously [n = 48], and the virtual SIT received six sessions simultaneously once a week for 60 min (n = 48) in pregnant women of 14-32 weeks' gestation referred to two selected hospitals. The primary outcome of this study was BSI-18 [Brief Symptom Inventory] and NuPDQ-17 [Prenatal Distress Questionnaire]. The secondary outcomes were the PSS-14 [Cohen's General Perceived Stress Scale]. Both groups completed questionnaires measuring anxiety, depression, pregnancy-specific stress, and generally perceived stress questionnaires before and after the treatment. Results The post-intervention results showed that the stress inoculation training technique in both VSIT and SIT interventions effectively reduced anxiety, depression, psychological distress, pregnancy-specific stress and general perceived stress [P < 0.01]. Also, the SIT interventions on decreasing anxiety [P < 0.001, η2 = 0.40], depression [P < 0.001, η2 = 0.52] and psychological distress [P < 0.001, η2 = 0.41] were more considerable than that of VSIT. However, There was no significant difference between SIT and VSIT intervention in terms of their effects on pregnancy-specific stress [P < 0.38, η2 = 0.01] and general stress [P < 0.42, η2 = 0.008]. Conclusion The semi-attendance SIT group has been a more effective and practical model than the VSIT group, for reducing psychological distress. Therefore, semi-attendance SIT is recommended for pregnant women.